1994
DOI: 10.1021/bk-1995-0582.ch007
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action of Allelochemicals in Allelopathy

Abstract: The primary mode of action has not been established for any allelopathic compound, albeit some physiological actions are known. The array of compounds cuts across many chemical classes, and it is unlikely they have a common mechanism of action. Allelochemicals active against higher plants are typically characterized as suppressing seed germination, causing injury to root growth and other meristems, or inhibiting seedling growth.A primary action on ATP production is indicated for the two quinones, juglone and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
170
0
30

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(212 citation statements)
references
References 77 publications
5
170
0
30
Order By: Relevance
“…The results obtained from testing the germination and root elongation revealed that inhibitory effect of hyssopus was stronger in T. aestivum than in C. sativus and confirmed the observations of Einhellig (1995) that plants may be selective in their responses to allelochemicals.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The results obtained from testing the germination and root elongation revealed that inhibitory effect of hyssopus was stronger in T. aestivum than in C. sativus and confirmed the observations of Einhellig (1995) that plants may be selective in their responses to allelochemicals.…”
Section: Discussionsupporting
confidence: 81%
“…There are also some data about the presence of water soluble allelopathic substances in aromatic plants (Ðikić, 2005;Economou et al, 2007). Allelochemicals may be selective in their action, or plants may be selective in their responses (Einhellig, 1995). So, determining the modes of action of allelochemicals is one of the challenging aspects in allelopathic studies (Chou, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous literature also indicated that the phenolic hydroxyl group engenders an inhibition effect on algal growth. Algal cells die because of the change in and destruction of the cell membrane structure by phenolic hydroxyl groups (Einhellig 1995;Everall and Lees 1997;Li et al 2010). This study demonstrated that there were chemically volatile substances in the different wood species.…”
Section: C) Eucalyptus Grandis × E Urophylla (D) Pinus Massoniana mentioning
confidence: 72%
“…Assim é esperado que estes flavonoides possam estar presentes na FAE, e desta forma é possível supor que tais efeitos do extrato e frações observados nos experimentos se devam em grande parte a estas substâncias. Estes compostos podem ser responsáveis, isolado ou sinergicamente, pela interferência nos processos fisiológicos durante a fase de desenvolvimento das espécies-alvo em estudo (Einhellig, 1986).…”
Section: Alface -L Sativa Lunclassified